Planning and Management of Patient Flow and Bed Capacities of Cardiac Ward with Mathematical Modeling and Discrete Event Simulation Approach - mohsen afsahi; Mohammad Mehdi Sepehri; ehsan ameri (Tehran University of Medical Sciences, 2015)
Background: Deciding on the number of hospital beds is one of the most serious challenges managers face. More hospital beds result in higher running cost although less hospital beds might cause disorder in patients flow.  Minimizing total cost besides maximizing the patients flow in a hospital network, considering the practical limitations is the main objective of this survey. Materials & Methods: This study had main steps to investigate following: identifying current limitations of changing capacity of each ward, by conducting interview with hospital managers and other personnel of Modares hospital, analyzing cardiac patient flow analysis, simulating current flow, determining practical scenarios and choosing the best among them by mathematical modeling could minimize total cost and maximize patient flow. Results: 31 practical scenarios have been determined and analyzed by surveying limitations among all existing scenarios. Finally, eight best scenarios had been selected. Results showed that decreasing the number of beds in CCU and increasing the number of beds in Post-CCU can improve patients flow, considering cost limitations.      Conclusion: A recommended approach in this study can be a general guide for capacity planning with taking practical limitations into consideration. This survey could be useful for the managers who are against the benefits of post CCU  by comparing the patient flow with and without this ward.